Characterization of a magneto-active membrane actuator comprising hard magnetic particles with varying crosslinking degrees. (October 2020) - Lee, Mina; Park, Taewoong; Kim, Chaemin; Park, Sung-Min
Abstract: We developed membrane actuators from magnetorheological elastomers (MREs) with hard magnetic particles using a novel mold-free fabrication procedure. The fabrication method improved the manufacturing efficiency via doctor blading and the two-stage curing process. To evaluate the performances of the membrane actuators, we monitored changes in the properties of the MREs in terms of the crosslinking degree in their polymeric matrices. The microstructure, curing behavior, magnetic properties, and mechanical properties of MREs were measured using a scanning electron microscope, vibrating sample magnetometer, rheometer, uniaxial tensile testing system. Deflection of the membrane actuators was measured using a custom-designed deflection system. The saturation magnetization ( M s ) and remanence ( B r ) of MREs decreased as the crosslinking degree of matrices increased. Their elastic moduli ( E ) also decreased as the crosslinking degree increased. Meanwhile, in case of integrated analysis, an anisotropic sample with an initial curing time of five minutes exhibited the largest actual deflection, although the particles were aligned with the magnetic fields after crosslinking of 6.01% was achieved. By identifying the relationship between the properties of MREs and the crosslinking degree in its polymeric matrix, the MREs used to fabricate membrane actuators can be tailored for specific applications: pumps, valves, microlenses, and cell stimulators. Graphical abstract: Unlabelled Image Highlights: The novel mold-free with doctor blading and two-stage curing improved production efficiency of a magneto-active actuator. The effect of matrix's crosslinking degree on magnetic and mechanical properties of the magneto-active actuator was analyzed. The stiffness, remanence and saturation magnetization increased as the first curing time shortened. Integrated analysis showed magneto-mechanical properties and emphasized the need for complex analyses to design the actuator.